1990
DOI: 10.1080/07399339009515917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a premenstrual syndrome education program on premenstrual symptomatology

Abstract: This exploratory study was conducted to determine the effects of an educational program on the number and severity of premenstrual symptoms as well as the number of premenstrual days with symptoms. Participants were a convenience sample of 47 employed women, whose scores on Abraham's Menstrual Symptomatology Questionnaire were in the moderate to severe range. Women were randomly divided into control and experimental groups, and those in the experimental groups participated in an education program. Both groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…But an increase in knowledge does not always cause behavior to change. 21,22 The present study was in agreement with Seidman (1990) 23 who stated that women's knowledge seemed to affect their practices during menstruation. In the existing Indian cultural milieu, the society is interwoven into a set of traditions, myths and misconceptions especially about menstruation and related issues.…”
supporting
confidence: 91%
“…But an increase in knowledge does not always cause behavior to change. 21,22 The present study was in agreement with Seidman (1990) 23 who stated that women's knowledge seemed to affect their practices during menstruation. In the existing Indian cultural milieu, the society is interwoven into a set of traditions, myths and misconceptions especially about menstruation and related issues.…”
supporting
confidence: 91%
“…Disagreement resulted in full text article retrieval. 27 trials were retrieved in full text to confirm eligibility and 14 proved potentially eligible [9, 10,14,15,16,17,18,19,20,26,27,28,29,30]. …”
Section: Resultsmentioning
confidence: 99%
“…and C.K.) collected all reported measures, including all domains, and grouped them into 6 discreet categories: anxiety [10, 15, 17, 20], behavioral changes [14, 16], depression [10,15,16,17,18, 20], interference [10, 16], sexual relations [10, 19], and water retention and edema [16, 17]. These groupings included outcome measures from all eligible trials except for the study by Corney et al [9] as this trial only reported an aggregate ‘premenstrual symptom score’.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations